Evaluation Of Conventional and Serological Methods for Rapid Diagnosis of Cryptococcal Meningitis in HIV Seropositive Patients at Tertiary Care Hospital - Hetal S Shah; Disha A Patel; Mahendra M Vegad (Medsci Publications, 2011)
Introduction: With the increase in the incidence of HIV infection, there is an increase in incidence of cryptococcal meningitis. Due to lack of sensitive methods for diagnosis, high morbidity and mortality are associated with the disease. Early and rapid diagnosis is essential to prevent serious complications. Objective: To know the prevalence of Cryptococcosis in HIV positive patients and to evaluate conventional methods with rapid serological diagnostic method. Methods : A total of 63 CSF samples of HIV seropositive hospitalized patients with history of meningitis were evaluated for Cryptococcus by India ink staining, culture and Cryptococcal antigen latex agglutination test(LAT) by CALAS. Results: Out of 63 CSF samples, prevalence of cryotococcosis were 9 (14.28%) by LAT, 7 (11.11%) by India ink preparation and 6 (9.5%) by culture. Sensitivity and specificity of India Ink is 83.3 % and 96.49 % and of latex agglutination test is 100 % and 94.7 % respectively considering culture as a gold standard. Discussion: Latex agglutination test is more sensitive than India ink test followed by culture. Conclusion: LAT is a simple, rapid and sensitive test for the early detection of cryptococcal antigen in clinical samples like CSF and may be considered as an aid in establishing diagnosis when culture is negative.